IRF8-Dependent Type I Conventional Dendritic Cells (cDC1s) Control Post-Ischemic Inflammation and Mildly Protect Against Post-Ischemic Acute Kidney Injury and Disease - Li, Na; Steiger, Stefanie; Fei, Lingyan; Li, Chenyu; Shi, Chongxu; Salei, Natallia; Schraml, Barbara U.; Zheng, Zhihua; Anders, Hans-Joachim; Lichtnekert, Julia (Frontiers in Immunology, 2021)
Post-ischemic acute kidney injury and disease (AKI/AKD) involve acute tubular necrosis and irreversible nephron loss. Mononuclear phagocytes including conventional dendritic cells (cDCs) are present during different phases of injury and repair, but the functional contribution of this subset remains controversial. Transcription factor interferon regulatory factor 8 (IRF8) is required for the development of type I conventional dendritic cells (cDC1s) lineage and helps to define distinct cDC1 subsets. We identified one distinct subset among mononuclear phagocyte subsets according to the expression patterns of CD11b and CD11c in healthy kidney and lymphoid organs, of which IRF8 was significantly expressed in the CD11blowCD11chigh subset that mainly comprised cDC1s. Next, we applied a Irf8-deficient mouse line (Irf8fl/flClec9acre mice) to specifically target Clec9a-expressing cDC1s in vivo. During post-ischemic AKI/AKD, these mice lacked cDC1s in the kidney without affecting cDC2s. The absence of cDC1s mildly aggravated the loss of living primary tubule and decline of kidney function, which was associated with decreased anti-inflammatory Tregs-related immune responses, but increased T helper type 1 (TH1)-related and pro-inflammatory cytokines, infiltrating neutrophils and acute tubular cell death, while we also observed a reduced number of cytotoxic CD8+ T cells in the kidney when cDC1s were absent. Together, our data show that IRF8 is indispensable for kidney cDC1s. Kidney cDC1s mildly protect against post-ischemic AKI/AKD, probably via suppressing tissue inflammation and damage, which implies an immunoregulatory role for cDC1s.